How Mothers in Poverty Explain Their Use of Corporal Punishment: A Qualitative Study in Kampala, Uganda. Issue 5 (November 2017) - Boydell, Nicola; Nalukenge, Winifred; Siu, Godfrey; Seeley, Janet; Wight, Daniel
Abstract Corporal punishment in the early years is associated with antisocial behaviour and violence, but little is known about its social and cultural context in low-income countries. This paper analyses how 12 deprived women in Kampala, Uganda, perceived corporal punishment, drawing on repeated semi-structured interviews. All thought it was sometimes necessary, for three main reasons. First, it was an important strategy to ensure good behaviour and maintain their and their child's, respectability, crucial to self-respect given severe poverty. Second, it was a means of establishing household routines and managing scarce resources. Third, it was a way to protect children from health risks. However, all mothers thought corporal punishment could be excessive, and most said it can be counter-productive, making children 'stubborn'. There appeared to be considerable variation in their degree of harsh parenting and emotional support. These findings could inform culturally appropriate interventions to reduce violence against children.